1999
DOI: 10.1148/radiology.210.2.r99fe15437
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pancreatic Transplant Rejection: Evaluation with Dynamic Contrast-enhanced MR Imaging Compared with Histopathologic Analysis

Abstract: Dynamic contrast-enhanced MR imaging is highly sensitive for the detection of acute pancreatic transplant rejection. Because of overlap of cases in the normal and rejection groups, percutaneous biopsy may be needed in some cases. Pancreatic allografts with infarction can be clearly identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…In our study, the percentage of enhancement in the normal allografts was greater, 120%, compared with 9% in the necrotic allografts. These results are similar to those of Fernandez et al [15] and Krebs et al [11].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In our study, the percentage of enhancement in the normal allografts was greater, 120%, compared with 9% in the necrotic allografts. These results are similar to those of Fernandez et al [15] and Krebs et al [11].…”
Section: Discussionsupporting
confidence: 93%
“…Small cohort studies have shown that MRI has become valuable in detecting pancreatic allograft complications [7][8][9][10][11][12][13]. Currently, in our institution, MRI is used as a second-line imaging modality for post- allograft patients who could not be adequately evaluated by CT or US.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations